The Empowerment of MSMEs through Islamic P2P Financing: A Value-Based Social Entrepreneurship Framework - Latifah, Leti; Rodoni, Ahmad; Aziz, Roikhan Mochamad (Universitas Muhammadiyah Yogyakarta, 2025)
Islamic Peer-to-Peer (P2P) financing has become a promising alternative to overcome capital barriers faced by Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. This study aims to examine the empowerment role of Islamic P2P financing through two complementary approaches. First, a descriptive qualitative method was employed to analyze the business models of Islamic P2P platforms and their integration with social entrepreneurship values. Second, a Systematic Literature Review was conducted to specifically assess the role of Islamic fintech in supporting MSME capitalization. The descriptive findings indicate that leading platforms such as ALAMI and Ammana integrate sharia contracts mudharabah, musyarakah, wakalah, and qardh to combine commercial goals with social impact. These practices reflect the principles of social entrepreneurship by enhancing inclusivity, ethical finance, and community empowerment. The SLR, based on 20 eligible articles published between 2019 and 2025, identified three main themes. First, models and financing schemes, including musyarakah, mudharabah, qardh al-hasan, and smart contracts that expand outreach and efficiency. Second, key success factors, such as trust, sharia compliance, literacy, technological innovation, and transparent information that drive adoption. Third, impact on financial inclusion and empowerment, highlighting contributions to MSME growth, poverty alleviation, inequality reduction, and integration with halal certification and community-based initiatives. Overall, the study confirms that Islamic P2P financing functions not merely as a financial intermediary but also as a driver of socio-economic transformation. Theoretically, it advances discourse on value-based financial innovation, while practically, it provides insights for policymakers, regulators, and practitioners to strengthen sharia fintech as a catalyst for MSME development and sustainable Islamic economic ecosystems.